International Transmission of Food Prices and Volatilities: A Panel Analysis - Hyun-Hoon Lee; Cyn-Young Park (Asian Development Bank (ADB), 2013)
High and volatile food prices pose a significant policy challenge around the world, and an understanding of the dynamics of food price inflation and volatility is essential in designing appropriate policy responses. Using the panel data for 72 countries from 2000 to 2011, the paper assesses the international transmission of food price inflation and volatilities as well as the effects of various internal and external factors on domestic food price inflation and volatility. The paper offers evidence in support of the international transmission of food price inflation and volatility. Specifically, the paper finds that the domestic food price inflation in Asia is strongly associated with the lagged value of global food price inflation (using the FAO food price index), while volatility spillovers from global to domestic food prices are rather contemporaneous. The paper also finds that both national food price inflation rates and volatilities are strongly associated with both intra- and extra- regional food price inflation rates and volatilities, respectively. The findings also suggest that higher economic growth rates, greater shares of food in merchandise imports, and smaller increases in the share of food in merchandise imports lead to lower domestic food price inflation. An appreciation of local currency, greater political stability, and higher income level are also found to lower domestic food price inflation. On the other hand, higher economic growth rates lead to lower volatilities of food prices.
hdl:11540/2072
Keywords: E31; F49; N50; N55; Q18; 330; Food price inflation; food price volatility; food price transmission; food security; food policy